The comparative study of geographically and demographically of the of animal protein consumption from livestock source - Ardi Novra; Fatati Fatati; Mulawarman Mulawarman (Syiah Kuala University, 2019)
Livestock is one of the important sources for protein in Jambi Province. However, the information on the consumption behavior of animal protein by local people was not available . Hence, the study aimed to analyze the behavior of consumption of protein sources from livestock between geographically and demographically separate regions.The researchsurveyconductedfor sixmonthsusingcross-section datawith the unitof analysisis the household. The multistage cluster random sampling(CRS) technique was used to selectthreetypes sub-districts(urban, migrantandnativerural) inthreedistrictsrepresentingthe western,central and eastern. The selected numbers of 150 householdswhere are allocatedequally with50electedforeach district. Simultaneous equationsmodel ofAIDS(Almost Ideal Demand System) was usedtoanalyze the difference inthe proportion ofconsumer spendingforfood material sources ofanimal protein from livestock. The AIDS model estimated bySeeminglyUnrelatedEquation (SUR) technique usingthe SAS/ETS9.12. The result showed that geographically, the household expenditure for eggs significantdifferencesamong the others and the highestoccur ineastern regions; while demographically, the household expenditure formeatin rural areas was significantly higher thanin the urban, but fordairysignificantly higher than in urban areas. The household expenditure for eggs more responsive to the other prices, but the meat more responsive to own and dairy prices. The same non-price factor was significantly influenced to all commodities for livestock products, and the relationship between eggandmeatcommodities weresubstituted, but with dairywascomplementary. It is concluded that demographic factors are more influential than geographic factors on the behavior of animal protein consumption from livestockKeywords: Geographically, Demographically, Livestock, Protein, AIDS